Effect of Oil Palm Empty Fruit Bunch Fiber Length on Flexural Performance and Macrostructure of Palmfiber Reinforced Concrete - Vedrix Vantri; Asfarizal (Jurnal Teknik Mesin, 2025)
This study investigates the influence of fiber length of oil palm empty fruit bunch (EFB) on the flexural performance and macrostructure of Palmfiber Reinforced Concrete (PRC) as a sustainable alternative to Glassfiber Reinforced Concrete (GRC). EFB fibers were selected due to their availability, environmental benefits, and potential to improve the mechanical properties of lightweight concrete. Five fiber lengths (3, 4, 5, 6, and 7 cm) were incorporated into PRC specimens. Flexural tests revealed that 5 cm fibers achieved the highest flexural strength of 11.78 kg/cm², while 4 cm fibers provided the maximum modulus of elasticity at 162.2 kg/cm². Macrostructural observations indicated satisfactory fiber–matrix bonding in most specimens; however, variations in fiber distribution and manual compaction affected overall performance. These findings demonstrate that fiber length significantly impacts the mechanical behavior of PRC, emphasizing the need for optimized production techniques to ensure consistent material quality.